Posted by **Anonymous** on Thursday, September 24, 2009 at 3:57pm.

Rewrite the equation so that y is the fucntion of x:

a. 1/7(49-7y)=5x-3y+14

b. 4(2x-3y)=-5(x+3y)

- math -
**Reiny**, Thursday, September 24, 2009 at 5:55pm
in the first, multiply each term by 7

49 - 7y = 35x - 21y + 98

14y = 35x + 49

y = (5/2)x + 7/2

the second is even easier, just expand, then re-arrange.

## Answer this Question

## Related Questions

- Algebra I - Rewrite the equation so that y is the fucntion of x: a. 1/7(49-7y)=...
- Algebra I - Rewrite the equation so that y is the fucntion of x: a. 1/7(49-7y)=...
- math - rewrite each equation as afunction of x.-3y+4y=11 Where are the equations...
- algebra - How do I rewrite this equation using radicals instead of rational ...
- algebra 116 - Rewrite the equation y = 5x – 2 as a function of x. This problem ...
- Logarithms - Kepler's third law of planetary motion relates P, the period of a ...
- math - Rewrite the following equation in the center-radius form of the equation...
- Math - Graph the linear equation 3y = 6x +3. Then rewrite the equation using the...
- Calculus - How do I rewrite log4 1=0 as an equivalent exponential equation? How ...
- Math - Use the point-slope form linear equation given to complete the following ...